ANALISIS EKSPRESI GEN BAX SEBAGAI PRO-APOPTOSIS PADA KULTUR SEL PUNCA ADIPOSA MESENKIMAL DENGAN PENAMBAHAN MADU (Tetragonula sp.) DAN ROYAL JELLY (Apis mellifera) - Nabila Nur Izzati (2023)
Adipose-derived Stromal/Stem Cells (ASCs) are mesenchymal stromal cells can be used as a therapeutic approach to degenerative diseases. ASCs were cultured on DMEM (Dulbecco's modified eagle) medium and FBS (Fetal bovine serum) as a cell supplement. The use of FBS can increase the risk of zoonotic diseases, so the addition of honey and royal jelly (HRJ) can help stimulate proliferation and reduce the risk of using FBS. Conversely, honey and royal jelly can also cause pro-apoptosis induced by the Bax gene. In this study, it aims to determine the expression of the Bax gene of ASCs culture on DMEM media with FBS supplements with the addition of honey (Tetragonula sp.) and royal jelly (Apis mellifera). The research design used is true experimental. There are 4 treatment groups, the first group is positive control, HJR treatment 0.1%, HJR treatment 0.05%, and negative control. Cell samples were taken from liposuction patients and cells were cultured at HRJ concentrations of 0.05% and 0.1%, then cells were analyzed using RT-PCR. The morphological results in the 10% FBS + 0.1% HRJ group were spindle-shaped and the cell density higher than the 10% FBS + 0.05% HRJ group. RT-PCR results found that Bax gene expression in group treatment with FBS 10% + HRJ is higher than positive control. Expression of gene Bax was higher in Group treatment FBS 10% + HRJ concentration of 0.05% than group FBS 10% + HRJ concentration of 0.1%. Relative gene Bax expression HRJ concentration group of 0.05% resulted in a 2.27-fold higher than in positive controls, and in group 0.1% concentration resulted in a 1.09-fold higher. So it can be concluded that honey and royal jelly in DMEM and FBS medium can induce Bax gene expression (p>0.05) thereby increasing pro-apoptosis.